The changing role of the regions in German technology policy - Dirk Dohse (European Regional Science Association (ERSA), 2002)
German technology policy has undergone a particularly remarkable change in recent years. Traditionally, the reference units of German technology policy were single firms, technologies or sectors. Since the mid-90`s the German Federal Government has discovered the region as a new reference unit for technology policy. Policy instruments such as the 'Bioregio contest', the 'City Contest Multimedia' or the 'Competition of Nanotechnology Competence Centers' have drawn a lot of attention nationally as well as internationally. In contrast to these early instruments that were restricted to single technologies, the newly established 'InnoRegio contest' encompasses different fields of technology but is geographically restricted to east Germany. The current paper analyses the two prototype models of the new region-oriented technology policy, namely the BioRegio contest and the InnoRegio contest as well as the most recent initiative 'Regional Innovative Growth Cores' which may be seen as a combination of the two prototype models. The aim is to elaborate strengths and weaknesses of region oriented technology policy in general and to make suggestions for it's advancement. Key words: Technology Policy, Regions, Competitiveness, Economic Geography, Clusters Jel-Classification: L52, O30, R11, R50.
Keywords: 330